Bacterial outer membrane vesicles as drug delivery carrier for photodynamic anticancer therapy - Jiang, Yuan; Zhou, ZunZhen; Liu, Chongzhi; Wang, Limei; Li, Chun (Frontiers in Chemistry, 2023)
Photodynamic Therapy (PDT) is an effective tumor treatment strategy that not only induces photocytotoxicity to kill tumor cells directly but also activates the immune system in the body to generate tumor-specific immunity, preventing cancer metastasis and recurrence. However, some limitations of PDT limit the therapeutic efficacy in deep tumors. Previous studies have used different types of nanoparticles (NPs) as drug carriers of photosensitizers (PSs) to overcome the shortcomings of PDT and improve therapeutic efficacy. Among them, bacterial outer membrane vesicles (OMVs) have natural advantages as carriers for PS delivery. In addition to the targeted delivery of PSs into tumor cells, their unique immunogenicity helps them to serve as immune adjuvants to enhance the PDT-induced immune effect, providing new ideas for photodynamic anticancer therapy. Therefore, in this review, we will introduce the biogenesis and anticancer functions of OMVs and the research on them as drug delivery carriers in PDT. Finally, we also discuss the challenges and prospects of OMVs as a versatile drug delivery carrier for photodynamic anticancer therapy.